2017
DOI: 10.1039/c6fo01532h
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre-based SCFA mixtures promote both protection and repair of intestinal epithelial barrier function in a Caco-2 cell model

Abstract: Impaired gut barrier function plays an important role in the development of many diseases such as obesity, inflammatory bowel disease, and in HIV infection. Dietary fibres have been shown to improve intestinal barrier function through their fermentation products, short chain fatty acids (SCFAs), and the effects of individual SCFAs have been studied. Here, different SCFA mixtures representing possible compositions from fibre fermentation products were studied for protective and reparative effects on intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 55 publications
5
87
0
1
Order By: Relevance
“…Previous studies have shown that L. salivarius produces abundant propionate/butyrate (16,17). Additionally, in previous studies, improved barrier function by SCFA was reported (18)(19)(20). SCFAs such as butyrate and acetate are known to protect intestinal barrier integrity by regulating through the activation of AMPK and TLR4.…”
Section: Lactobacillus Salivarius Bp121 Prevents Cisplatin-induced Acmentioning
confidence: 90%
“…Previous studies have shown that L. salivarius produces abundant propionate/butyrate (16,17). Additionally, in previous studies, improved barrier function by SCFA was reported (18)(19)(20). SCFAs such as butyrate and acetate are known to protect intestinal barrier integrity by regulating through the activation of AMPK and TLR4.…”
Section: Lactobacillus Salivarius Bp121 Prevents Cisplatin-induced Acmentioning
confidence: 90%
“…Likewise, the protein expression of ZO‐1, occludin, and claudin‐1 was significantly reduced in IPEC‐J2 cells exposed to heat for 72 hr. Because the single‐cell layer of the intestinal epithelium constitutes the largest and most important barrier (T. Chen et al, 2017), heat exposure‐induced intestinal barrier damage is attributable, at least in part, to the inhibition of cell proliferation and the induction of cell apoptosis. Nevertheless, it is worth noting that the intestinal barrier dysfunction is not specific to heat‐exposure damage.…”
Section: Discussionmentioning
confidence: 99%
“…24 FITC-D4 was added to the apical chamber at the end of treatment. The insert area was 0.33 cm 2 and the pore size was 0.4 µm.…”
Section: Determination Of Teer and Fitc-d4mentioning
confidence: 99%
“…Fluorescein isothiocyanate-dextran (FITC-D4, 4 kDa, 0.25 mM) measurements were taken for paracellular permeability. 24 FITC-D4 was added to the apical chamber at the end of treatment. After 2 hours, 50-µL medium from the bottom chamber were transferred to a fluorescence measurement plate, and fluorescence intensity was measured at an excitation wavelength of 485 nm and emission wavelength of 530 nm.…”
Section: Determination Of Teer and Fitc-d4mentioning
confidence: 99%